Potensi Antimikroba dan Antioksidan Beberapa Ekstrak Daun Benalu (Scurrula ferruginea (Roxb. ex Jack) Danser dari Archidendron sp. terhadap Staphylococcus aureus, Escherichia coli, dan Candida albicans - Apriyelita, Annisa; Periadnadi, Periadnadi; Nurmiati, Nurmiati (Bioscientist : Jurnal Ilmiah Biologi, 2024)
Scurrula ferruginea (Roxb. ex Jack) Danser is known for its role as an antimicrobial and antioxidant agent due to its content of phenolic compounds, alkaloids, and terpenoids. S. ferruginea has been widely used in traditional medicine for skin infections, diarrhea, hypertension, and digestive tract diseases. This study aims to determine the antimicrobial and antioxidant potential of various treatments of S. ferruginea mistletoe extracts. The experimental method used in this research is the nested pattern experiment. The extract treatments applied include fresh extract, boiled dry extract, boiled fresh extract, brewed dry extract, and brewed fresh extract. Antimicrobial potential was assessed using disc diffusion and dilution methods. Antioxidant activity (IC50) was determined using the DPPH (1,1-Diphenyl-2-Picryl-Hydrazine) method, and Total Phenolic Content (TPC) was also determined. The results indicate that the highest antimicrobial activity against Escherichia coli and Staphylococcus aureus was found in the strong category of fresh extract treatment, whereas there was no significant effect on Candida albicans growth. The fresh extract treatment exhibited the highest antimicrobial activity with a total phenolic content of 20.77321 mgGAE/mL. The Minimum Inhibitory Concentration (MIC) values for the fresh extract against S. aureus and E. coli were 6.25%, and the Minimum Bactericidal Concentration (MBC) values were 12.5% against both bacteria. The antioxidant value of the fresh extract was 101.26 Î¼g/mL, categorized as moderate. Based on the conducted research, it can be concluded that S. ferruginea leaf extract can inhibit the activities of S. aureus and E. coli, while showing no effect on Candida albicans growth.